Insomnia and stress of physicians during COVID-19 outbreak (2020)
Background: Healthcare workers are at high risk of developing sleep disorders during an outbreak. This study aimed to measure severity of sleep difficulty and its correlation with duration of deal with suspected/confirmed cases of novel coronavirus (COVID-19) in physicians. Methods: In this cross-sectional study, 268 physicians from different medical settings were included during the COVID-19 outbreak. Results: The mean age and experience of physicians were 35.06 (33e70 years) and 10.13 years. The median duration of dealing with suspected/confirmed cases of COVID-19 was 1.0 (0e30 days). The mean sleep score and stress of physicians were 8.43 of 24.0 and 4.20 of 10, respectively. More than two-thirds of the physicians were sleepless (68.3%) and majority had stress (93.7%). The study did not find a significant difference in sleep score of physicians with different specialties (P ¼ 0.059). However, most physicians were sleepless; including anesthesia and intensive care (77.8%); general physicians (80.8%), and obstetrics and gynecology (80.0%). They were sleepless in morning (58.7%); evening (77.8%); night (100%); and multi-shift (70.9%). The physicians who dealt with suspected or confirmed cases of COVID-19 or with stress had more escalated sleep compared to those who did not deal with patients or without stress (9.39 vs. 7.17 and 8.78 vs. 2.69 P < 0.001). The sleep of physicians was escalated with increasing stress (r ¼ 0.558; P < 0.001) and a number of days that physicians dealt with suspected/confirmed cases of COVID-19 (r ¼ 0.210; P ¼ 0.001), respectively. Conclusion: The study confirmed that working with COVID-19 patients has a negative effect on the sleep of physicians.